The computational psychiatry of reward: broken brains or misguided minds? - Moutoussis, M.; Story, G. W.; Dolan, R. J. (Frontiers in Psychology, 2015)
Research into the biological basis of emotional and motivational disorders is in danger of riding roughshod over a patient-centred psychiatry and falling into the dualist errors of the past, i.e. by treating mind and brain as conceptually distinct. We argue that a psychiatry informed by computational neuroscience, computational psychiatry, can obviate this danger. Through a focus on the reasoning processes by which humans attempt to maximise reward (and minimise punishment), and how such reasoning is expressed neurally, computational psychiatry can render obsolete the polarity between biological and psychosocial conceptions of illness. Here, the term 'psychological' comes to refer to information processing performed by biological agents, seen in light of underlying goals. We reflect on the implications of this perspective for a definition of mental disorder, including what is entailed in asserting that a particular disorder is ‘biological’ or ‘psychological’ in origin. We propose that a computational approach assists in understanding the topography of mental disorder, while cautioning that the point at which eccentric reasoning constitutes disorder often remains a matter of cultural judgement.